1994
DOI: 10.1055/s-2007-1021052
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Heart Rate Threshold, Lactate Turn Point and Myocardial Function

Abstract: We examined the relationship between heart rate threshold (HRT), lactate turn point (LTP) and myocardial function expressed as left ventricular ejection fraction (LVEF) determined by radionuclide ventriculography. Two groups of subjects (G I: N = 8; G II: N = 7) with and without a deflection of heart rate performance curve (HRPC) underwent sitting cycle ergometry. HRT (G I), aerobic threshold (AeT; G I, G II), and LTP (G I, G II) were determined by means of linear regression break point analysis. Also, a break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 17 publications
4
37
0
5
Order By: Relevance
“…Therefore, blood pressure monitoring devices that are hardly influenced by body motions and vibrations are used in laboratoies [1][2][3][4][5][6] . However, by our results, we have shown that in an exercise tolerance test, the DPBP can be derived with a portable sphygmomanometer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, blood pressure monitoring devices that are hardly influenced by body motions and vibrations are used in laboratoies [1][2][3][4][5][6] . However, by our results, we have shown that in an exercise tolerance test, the DPBP can be derived with a portable sphygmomanometer.…”
Section: Discussionmentioning
confidence: 99%
“…The anaerobic threshold (AT) determined by expired gas analysis and the lactate threshold (LT) obtained by lactate measurement are useful not only for the measurement of physical fitness in athletes but also as indices of health in middle-aged and older individuals, and of optimal exercise intensity in patients with diabetes mellitus, ischemic heart disease, or stroke [1][2][3][4][5][6] . However, these approaches require an expensive expired gas analyzer and frequent blood sampling, and thus are difficult to implement at clinical sites of physical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The anaerobic threshold (AT) determined by expired gas analysis and the lactate threshold (LT) obtained by lactate measurement are useful not only for the measurement of physical fitness in athletes but also as indices of health in middle-aged and older individuals, and of optimal exercise intensity in patients with diabetes mellitus, ischemic heart disease, or stroke [1][2][3] . However, their evaluation require an expensive expired gas analyzer and frequent blood sampling; thus, they are difficult to implement in clinical physical therapy settings.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies reported arrhythmias, and there have been numerous studies reporting oxygen uptake kinetics and heart rate threshold in relation to exercise tolerance, gender and age [3][4][5][6][7][8][9] . However, we have found no previous reports of DPBP in relation to gender and age.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac rehabilitation programs are based on electrocardiography, cardiac ultrasonography, angiography, and evaluation of exercise tolerance to measure the anaerobic threshold using oxygen uptake kinetics [1][2][3][4][5][6][7][8][9][10][11][12][13] . Tanaka et al 8) developed the DPBP method, a simple method for measuring the anaerobic threshold (AT) and lactate threshold (LT).…”
Section: Introductionmentioning
confidence: 99%